Globalization and Drug and Alcohol Use in Rural Communities in Nigeria: A Case Study - Fiki, Charles (2007)
This paper presents an exploratory study of alcohol and drug use in two rural communities in Plateau State, Nigeria. The aim is to raise awareness of the rural alcohol and drug problem. The paper examines the patterns of alcohol consumption and drug use, and their perceived functions for substance use among rural farmers in Nigeria. The study shows the common use of marijuana and alcohol in addition to prescription drugs. There is also evidence of multiple or combinational drug use. Pleasure and relaxation emerged as the major reasons for drug and alcohol use. Factors influencing alcohol and drug use are the relative neglect of rural communities, and the activities of hawkers, quacks, and other untrained individuals pervading the rural health sectors. The paper calls for further research to adequately capture the reality of alcohol and drug use in rural communities in Nigeria